Prinsip Norma-norma Bertutur yang Beretiket dan Beretika dalam Alquran - Shafruddin Tajuddin (Al-Ma‘rifah, 2015)
In linguistic norms, the language of the Quran consists of words, sentences, and paragraphs which are full of meaning. Therefore, based on this aspect, it can be approximated as the other text that can be studied and researched through linguistic elements, as expressed in the form of linguistic structure, both textual and contextual. The language of the Quran is no longer just words, phrases, and sentences as a reading routines Muslims, but also as a sign and message and also information to communicate our Mankind that in the texts of the Quran contained linguistic discourse strands of substitutions. Therefore, this research is an ethnographic study of communication that is qualitative descriptive, and the problem is focused directly to the principles of spoken norms as the main observation variable or formal object, and can be formulated "How are tagged spoken norms and ethics in the Quran?". The purpose of this study was to reveal concretely about the principles the ethical norms and tagged speak contained in the Qur'an. The data contains the discourse of substitutions on the linguistic text of the Quran, searched and analyzed using the ethnographic instrument of communication. This means that this study is based on the theory of speech ethnography or the ethnography of communication with the concept of the English acronym "SPEAKING". The data from the language text of the Quran are discussed in this study showed the disclosure principles of tagged spoken norms and ethics in the Qur'an. This means that the discussion proved that the verses that speak of substitutions are principles, beliefs, attitudes, doctrines, and guidelines for how to speak with etiquette and ethical speech principles. This principle is universal for anyone and in any language. This is so that communication can take place with a good and harmonious.